Assessment of the reliability and validity of the Lactate Pro lactate analyser - Psycharakis, S.; Cooke, C.; O'Hara, J.; Siems, A. (Biomechanics and Medicine in Swimming IX, 2003)
This study assessed the reliability and repeatability of a portable hand held lactate analyser commonly used in swimming [Lactate Pro (LP)] against a well-established analyser [Analox analyser P GM7 (AN)]. The results of the present study indicated that the accuracy, reliability and validity of the LP device is questionable, whereas the AN was found to have good repeatability. In conclusion, the limitations of the LP device, in terms of validity and reliability, should be considered before it is used to measure BLa values during exercise.